2021
DOI: 10.21467/ajgr.10.1.23-32
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Feeding Gases on the Composition of Plasma Activated Water

Abstract: As we are all aware that “PLASMA” is the fourth state of matter and about 99% of the universe comprises of plasma. Plasma invariably consists of essential reactive oxygen and nitrogen species which are necessary for agricultural purposes thus making it an interesting subject for research. When water is exposed to plasma arc, its composition changes and forms Plasma Activated Water (PAW). Research studies have proved PAW to be an effective disinfectant and also providing imperative nutrients to plants. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…(2019) reported that H 2 O 2 was abundantly detected in the PALs, and its concentration increased with the presence of oxygen in the working gas. Additionally, the composition of the reactive species also varies greatly depending on the type of plasma source used (Baik et al., 2013; Thati et al., 2021). According to Smet et al.…”
Section: Plasma‐activated Liquidsmentioning
confidence: 99%
“…(2019) reported that H 2 O 2 was abundantly detected in the PALs, and its concentration increased with the presence of oxygen in the working gas. Additionally, the composition of the reactive species also varies greatly depending on the type of plasma source used (Baik et al., 2013; Thati et al., 2021). According to Smet et al.…”
Section: Plasma‐activated Liquidsmentioning
confidence: 99%
“…Previous research on the application of plasma in agriculture has shown the presence of O radicals plays a pivotal role in promoting plant germination and growth. [38][39][40][41][42] Furthermore, the CI was employed to evaluate the effectiveness of oxidation initiated by oxygen-based reactive species produced by both the LF-PJ and LFMHP. CI unveiled a color change from purple to green after exposure to the plasma indicating the etching effect of oxygen radicals which are known to contribute to the enhancement of plant growth and germination.…”
Section: Characteristics Of Lfmhpmentioning
confidence: 99%
“…This method enables the direct application of treatment to plants while overcoming the constraints imposed by tools and equipment. [34][35][36][37][38][39][40][41][42][43] To obtain information on the essential species that contribute to improving seed germination and plant growth, PAW was generated by applying both LF-PJ and LFMHP techniques, utilizing a discharge gas mixture of Ar-O 2 . The oxidation efficiency of reactive oxygen species was assessed in LF-PJ and LFMHP utilizing chemical indicators (CIs), allowing for the investigation of the reactive species generated in this study.…”
Section: Introductionmentioning
confidence: 99%
“…27 While other reactions are possible with helium, argon, and carbon dioxide, the RONS reactions drive the key chemistry for plasma activated water. 17,28 The specific composition of RONS is a key aspect for the potential applications of any PAW production, as the pH and conductivity are each affected by the different species. The pH is often lowered by the RNS.…”
Section: Introductionmentioning
confidence: 99%